TASK AND MANAGEMENT SUPERVISION OF GUIDANCE AND COUNSELING - Anjar, Tri (Universitas Muhammadiyah Metro, 2014)
Abstract: Improving the quality of guidance and counseling services in the educational unit requires the support of other parties. Process guidance and supervision right, and carried out by competent and professional personnel are needed to support the quality of counseling services performed by teachers BK. BK control activities include activities supervisor, educator, and motivator. The pattern of structured supervision, honest, and based on the analysis of the problems the ministry guidance and counseling in schools, will be able to give a good contribution to the improvement, evaluation, and improvement of guidance and counseling services, as well as the professionalism of teachers BK as a service provider.Keyword: guidance, counseling, supervision, management